Legal Analysis of Criminalization of Children Perpetrators of the Crime of Theft with Aggravation Based on Pancasila Justice (Criminal Case Study Decision Number: 57/Pid.B/2024/PN Nab) - Satria, Rifai Ermin; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Law is a norm or rule that contains mandatory legislation and anyone who violates the article will receive legal sanctions. The legal subjects who are to be prosecuted are not only those who have actually committed unlawful acts, but also legal acts that may arise and equip the state to act in accordance with the laws currently in force. Crime is an offense, namely things that are contrary to or in conflict with the legal principles that are the beliefs of human life and are not bound by law. Crimes that often occur in society lately include robbery, burglary, murder and rape. One type of crime that often occurs in society is theft. The crime of theft is a crime that is officially stipulated as prohibited and punishable, in this case it is an act defined as "stealing". If translated from the word "zich toeeigenen" it is "to control", because after discussing the numbers, the reader will understand that "zich toeeigenen" has a very different meaning from the meaning of "owning" which is clearly widely used and widely known until now in the Criminal Code which has been translated into Indonesian in the article, even though it is true that the statute of "ownership" itself is also included in the meaning of "zich toeeigenen" as understood in Article 362 of the Criminal Code. The case in Decision Number 57/Pid.B/2024/PN Nabire relates to a criminal act of aggravated theft that occurred on Tuesday, March 5, 2024 at around 04.00 WIT, at Jalan Mongonsidi RT/RW 002/003, Oyehe Village, Nabire District, Nabire Regency. The defendant Andika Wisnu Wijaya together with Child Witness ISBA PELLU alias IBAX (who was processed in the child case file Number 4/Pid.Sus-Anak/2024/PN Nap), as well as two other people who currently have DPO status, namely Brian Rumbewas and Sedek Kum, committed the theft together. The perpetrators used two motorbikes to get around and monitor the location. When crossing Jalan Mongonsidi, they saw the window of the boarding house open, then decided to commit the theft.